THE SOCIAL AND POLITICAL ROLE AND EDUCATIONAL SIGNIFICANCE OF PUBLIC HOLIDAYS IN UZBEKISTAN - Ilhom Sodiqov (Western European Studies, 2025)
This article examines the emergence of holidays in Uzbekistan today, along with social and political reforms, ancient traditions, their significance, and educational value for society.
Keywords: Field performance; holiday; Navruz